Life Stories From Children Working in Bangladesh’s Leather Sector and its Neighbourhoods: Told and Analysed by Children - Sayem, Mashrique; Sayed, Sayma; Maksud, A. K. M.; Reaz Hossain, Khandaker; Afroze, Jiniya; Burns, Danny; Raw, Anna; Hacker, Elizabeth (CLARISSA Research and Evidence Paper, 2023)
CLARISSA (Child Labour: Action-Research-Innovation in South and South-Eastern Asia) has a participatory and child-centred approach that supports children to gather evidence, analyse it themselves and generate solutions to the problems they identify. The life story collection and collective analysis processes supported children engaged in the worst forms of child labour in Bangladesh to share and analyse their life stories. Over 400 life stories were collected from children who worked in the leather supply chain, or who lived and worked in leather sector neighbourhoods. Using causal mapping, 53 children who were engaged in or had experience of the worst forms of child labour collectively analysed the data. This resulted in children’s life stories becoming the evidence base for revealing macro‑level system dynamics that drive the worst forms of child labour. This paper is a record of the children’s analysis of the life stories and key themes they identified, which formed the basis of a series of seven child-led Participatory Action Research groups.

Fast Forwarding to Systems Maps of Corruption: Getting to Usable Analysis More Quickly - Woodrow, Peter (CJL, 2023)
For AC practitioners, systems mapping is essential but also difficult. To lessen obstacles, Peter Woodrow proposes a scaffolded approach. An Experiment in “Fast Forwarding” Drawing upon our near-decade work on corruption, we recently decided to try an experiment: we would present “common patterns” of corruption as tentative models to adapt and add to—rather than try to teach people to do systems mapping from scratch. In this teaching experiment, each common pattern would function as a kind of “scaffolding” or framework that participants can build on to generate a cogent systems map as the basis for identifying possible points of intervention and subsequent program planning.

Adaptive Evaluation: A Complexity-based approach to Systematic Learning for Innovation and Scaling in Development - Gokhale, Siddhant; Walton, Michael (CID Faculty Working Paper, 2023)
Nearly all challenges in international development tend to be complex because they depend on constantly evolving human behaviour, systems, and contexts, involving multiple actors, entities, and processes. As a result, both the discovery and scaling of innovations to address challenges in development often involve changes in system behaviour or even system-level transformation. This is rarely a linear process over time and can result in unexpected outcomes. Existing evaluation techniques commonly used in international development, including Randomized Control Trials (RCT) and quasi-experimental methods, are good at assessing specific effects of interventions but are not designed for the change processes inherent to innovation and scaling within a system. There is a need to reconstruct how we use existing measurement tools, techniques, and methodologies so that they capture the complexity of the environment in which an intervention or change occurs. We introduce Adaptive Evaluation, designed to learn at various levels of complexity while supporting the transformation needed to foster sustainable change. An Adaptive Evaluation uses three main approaches to work with complex questions—systems diagnosis, theorybased assessment of change processes, and iterative designs. An Adaptive Evaluation typically builds hypotheses from field-based interactions, emphasizes learning over testing, advocates open-mindedness with techniques, and appreciates the value of dialogue and participation in navigating complex processes. It can use RCT or similar techniques to analyse specific processes within a system or a development cycle, but these are embedded in a broader approach to assessment and interpretation. It is designed to be flexible and adjust to shifting contexts. Finally, an Adaptive Evaluation can be applied at any stage in a complex intervention's lifecycle, from the interpretation of the system and change processes to rapid experimentation, prototyping, and testing of select interventions, and then adaptation to different settings for impact at scale. This paper provides the theoretical basis for an Adaptive Evaluation—the main approaches, core ideology, process, and applications.

Learning from Life Story Collection and Analysis With Children Who Work in the Worst Forms of Child Labour in Nepal - Karki, Shanta; Apgar, Marina; Snijder, Mieke; Sharma, Ranjana (CLARISSA Learning Note, 2022)
The CLARISSA Nepal team collected and analysed 400 life stories of children and young people engaged in or affected by the worst forms of child labour (WFCL), particularly in the “Adult Entertainment” sector in Nepal, which includes children working in Dohoris (restaurants playing folk music), dance bars, spa-massage parlours, khaja ghars (tea/snack shop) and guest houses. Stories were also collected from children in CLARISSA’s focus neighbourhoods, children in this category include street connected children and those working in transportation, party palaces, domestic labour and construction sites. Of the 400 stories collected, 350 were collected by adult researchers and 50 were collected by children themselves.

System Change: A Guidebook for Adopting Portfolio Approaches - Wellsch, Brent (UNDP, 2022)
This guidebook codifies the principles and methods of applying systems change and portfolio approaches to complex development challenges with practical tools and examples. It is based on the empirical learning generated from the collaborative initiatives in UNDP Country Offices in Bhutan, Pakistan, the Philippines, and Viet Nam with support from Regional Innovation Centre for Asia and the Pacific.

Ripple effects mapping: capturing the wider impacts of systems change efforts in public health - Nobles, James; Wheeler, Jessica; Dunleavy-Harris, Kirsty; Holmes, Richard; Inman-Ward, Alan; Potts, Alexandra; Hall, Jennifer; Redwood, Sabi; Jago, Russell; Foster, Charlie (BMC Medical Research Methodology, 2022)
Systems approaches are currently being advocated and implemented to address complex challenges in Public Health. These approaches work by bringing multi-sectoral stakeholders together to develop a collective understanding of the system, and then to identify places where they can leverage change across the system. Systems approaches are unpredictable, where cause-and-effect cannot always be disentangled, and unintended consequences – positive and negative – frequently arise. Evaluating such approaches is difficult and new methods are warranted.
Keywords: Complex adaptive systems; Complexity; Evaluation; Public health; Systems approach; Systems science

A Systems Framework for International Development: The Data-Layered Causal Loop Diagram - Blair, Courtney; Gralla, Erica; Wetmore, Finley; Goentzel, Jarrod; Peters, Megan (Production and Operations Management, 2021)
Meeting the United Nations Sustainable Development Goals (SDGs) will require adapting or redirecting a variety of very complex global and local human systems. It is essential that development scholars and practitioners have tools to understand the dynamics of these systems and the key drivers of their behavior, such as barriers to progress and leverage points for driving sustainable change. System dynamics tools are well suited to address this challenge, but they must first be adapted for the data-poor and fragmented environment of development work. Our key contribution is to extend the causal loop diagram (CLD) with a data layer that describes the status of and change in each variable based on available data. By testing dynamic hypotheses against the system's actual behavior, it enables analysis of a system's dynamics and behavioral drivers without simulation. The data-layered CLD was developed through a 4-year engagement with USAID/Uganda. Its contributions are illustrated through an application to agricultural financing in Uganda. Our analysis identified a lack of demand for agricultural loans as a major barrier to broadening agricultural financing, partially refuting an existing hypothesis that access to credit was the main constraint. Our work extends system dynamics theory to meet the challenges of this practice environment, enabling analysis of the complex dynamics that are crucial to achieving the SDGs.

Applying Power Analysis: Using the ‘Powercube’ to explore forms, levels and spaces - Gaventa, John (Power, Empowerment and Social Change, 2019)
In a complex, globalised and rapidly changing world, power dynamics are multidimensional, constantly evolving, and full of complexity. The ‘powercube’ (Gaventa, 2006) is an approach to power analysis which can be used to examine the multiple forms, levels and spaces of power, and their interactions. Building on earlier work on power, and elaborated and popularised in collaboration with other colleagues through the web site powercube.net and numerous other resources, the powercube has been widely used around the world for analysis of power, education and awareness building, context analysis, programme and strategy development, and monitoring and evaluation. This article briefly outlines the evolution of the powercube, and provides examples of the issue areas in which it has been used, and for what purposes. Drawing on these, we then offer eight lessons of how to apply the powercube framework for analysing and transforming power relations.

Towards ‘Targeted Systems Change’ - Rye, Sam (Fieldnotes by Sam Rye, 2019)
Modelling and communicating how to shift systems

Causal Loop Diagrams: Little Known Analytical Tool | iSixSigma - Rushing, William (2010)
The causal loop diagram is an analytical tool that is seldom used in Six Sigma but nonetheless is still very valuable. It is a foundational tool used in system dynamics, a method of analysis used to develop an understanding of complex systems.

Thinking in Systems: A Primer - Meadows, Donella H. (Chelsea Green Publishing, 2008)
In the years following her role as the lead author of the international bestseller, Limits to Growth—the first book to show the consequences of unchecked growth on a finite planet— Donella Meadows remained a pioneer of environmental and social analysis until her untimely death in 2001.Thinking in Systems, is a concise and crucial book offering insight for problem solving on scales ranging from the personal to the global. Edited by the Sustainability Institute’s Diana Wright, this essential primer brings systems thinking out of the realm of computers and equations and into the tangible world, showing readers how to develop the systems-thinking skills that thought leaders across the globe consider critical for 21st-century life.Some of the biggest problems facing the world—war, hunger, poverty, and environmental degradation—are essentially system failures. They cannot be solved by fixing one piece in isolation from the others, because even seemingly minor details have enormous power to undermine the best efforts of too-narrow thinking.While readers will learn the conceptual tools and methods of systems thinking, the heart of the book is grander than methodology. Donella Meadows was known as much for nurturing positive outcomes as she was for delving into the science behind global dilemmas. She reminds readers to pay attention to what is important, not just what is quantifiable, to stay humble, and to stay a learner.In a world growing ever more complicated, crowded, and interdependent, Thinking in Systems helps readers avoid confusion and helplessness, the first step toward finding proactive and effective solutions.